2013
DOI: 10.1371/journal.pone.0069506
|View full text |Cite
|
Sign up to set email alerts
|

Serum TRPM1 Autoantibodies from Melanoma Associated Retinopathy Patients Enter Retinal ON-Bipolar Cells and Attenuate the Electroretinogram in Mice

Abstract: Melanoma-associated retinopathy (MAR) is a paraneoplastic syndrome associated with cutaneous malignant melanoma and the presence of autoantibodies that label neurons in the inner retina. The visual symptoms and electroretinogram (ERG) phenotype characteristic of MAR resemble the congenital visual disease caused by mutations in TRPM1, a cation channel expressed by both melanocytes and retinal bipolar cells. Four serum samples from MAR patients were identified as TRPM1 immunoreactive by 1. Labeling of ON-bipolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…Vitamin A deficiency Paraneoplastic syndrome: melanoma-associated retinopathy characterized by an ON-bipolar defect with anti-TRPM1 antibodies found in the sera of some patients (Dhingra et al, 2011;Kondo et al, 2011;Morita et al, 2014;Xiong et al, 2013) -Of infantile nystagmus (Gottlob and Proudlock, 2014;Pieh et al, 2008) CSNB genotypeephenotype correlation, since so far genes involved in icCSNB affect proteins at the presynaptic level, impacting both ONand OFF bipolar signalling, while cCSNB affects post synaptic ONbipolar function. Fundus examination is usually normal apart from myopic changes.…”
Section: -Of Night Blindnessmentioning
confidence: 99%
“…Vitamin A deficiency Paraneoplastic syndrome: melanoma-associated retinopathy characterized by an ON-bipolar defect with anti-TRPM1 antibodies found in the sera of some patients (Dhingra et al, 2011;Kondo et al, 2011;Morita et al, 2014;Xiong et al, 2013) -Of infantile nystagmus (Gottlob and Proudlock, 2014;Pieh et al, 2008) CSNB genotypeephenotype correlation, since so far genes involved in icCSNB affect proteins at the presynaptic level, impacting both ONand OFF bipolar signalling, while cCSNB affects post synaptic ONbipolar function. Fundus examination is usually normal apart from myopic changes.…”
Section: -Of Night Blindnessmentioning
confidence: 99%
“…TRPM1 is also identified as a target of an anti-bipolar cell antibody produced in a patient with paraneoplastic vitelliform retinopathy, which is a MAR-like retinopathy (Wang et al 2012). A recent study reported that TRPM1 autoantibodies from MAR patient sera bind to an epitope in the intracellular N-terminal domain of the TRPM1 channel and that intravitreal injection of autoantibodies reduces the ERG b-wave in mouse eyes, although no specific autoantibody immunoreactivity was demonstrated using Western blot analysis (Xiong et al 2013). These observations, the expression of TRPM1 in melanocytes and its downregulation in melanoma cells, suggest that TRPM1 is one of the retinal autoantigens in some CAR or MAR associated with retinal ON-bipolar cell dysfunction (Duncan et al 1998).…”
mentioning
confidence: 99%
“…This region of TRPM1 is 91% identical between the mouse and human sequences, and we have previously demonstrated that human MAR sera react with mouse TRPM1 by immunofluorescent labeling of mouse retina sections and CHO cells transfected with mouse TRPM1. 6,25 Though both MAR sera react well with mouse TRPM1 by immunofluorescence, both sera reacted more strongly with human TRPM1 than mouse TRPM1 by Western blotting (Fig. 1C).…”
Section: Resultsmentioning
confidence: 91%
“…6 To localize the MAR epitope further, we subcloned successively smaller mouse TRPM1 cDNA restriction fragments and expressed them as EGFP fusion proteins in transfected HEK293 cells (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%